(3BdjGJ ecGaMI GdJdGYH aj CSYGQ GdChQGb GdeGdjI (B:s (3OQGSI aj GdbGfhf GdeUQj hGdchjJj hGdEfLdjRj (B/s - (3SeQ UdGM YHO Gddg YHO Gddgs; (3Ndjd ajcJhQ JGOQSs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2022)
(3jbhV GdJdGYH aj CSYGQ GdChQGb GdeGdjI KbI GdeSJKeQjf aj fRGgI CShGb GdeGd hJcGedgG(B. (3hjfUQa eaghe GdJdGYH aj GdCSYGQ aj eLGd GdCShGb GdeGdjI Edi GdJUQaGJ GdJj jbhe HgG eJOGhd Ch eLehYI ef GdeJOGhdjf HgOa EMOGK aQb ebUhO eG Hjf SYQ GdhQbI GdeGdjI hbjeJgG GdMbjbjI, dJMbjb CQHGM ZjQ eTQhYI Ch JLfH NSGFQ Ydi MSGH HbjI GdeJOGhdjf aj GdShb GdeGdjI(B. (3hfXkQG deG jTcdg GdJdGYH aj CSYGQ GdChQGb GdeGdjI ef XGgQI NWjQI JfNQ GdCShGb GdeGdjI aj GdOhd GdfGejI hGdeJbOeI, abO HGJ ef GdVQhQj GdHMK Yf GdBdjGJ GdCcKQ fLGYI haGYdjI ddhbGjI efg hecGaMJg(B. (3dPdc LGAJ gPg GdOQGSI ehbhaI Ydi ehVhY(B: ((3BdjGJ ecGaMI GdJdGYH aj CSYGQ GdChQGb GdeGdjI(B: (3OQGSI aj GdbGfhf GdeUQj hGdchjJj hGdEfLdjRj(B). (3hJfGhd GdHGMK aj GdHGH GdChd GdSjGSGJ GdJTQjYjI aj JYQja GdJdGYH aj CSYGQ GdChQGb GdeGdjI, hobSe gPG GdHGH Edi aUdjf; GdChd oNUU dHjGf eGgjI GdJdGYH aj GdCSYGQ aj eLGd GdCShGb GdeGdjI, CeG GdKGfj aoNUU dJejjR GdJdGYH aj CSYGQ GdChQGb GdeGdjI Yf GdeeGQSGJ ZjQ GdeTQhYI GdCNQi GdJj bO JJTGHg eYg(B. (3CeG GdHGH GdKGfj ef gPg GdOQGSI, acGf dHjGf SHd MeGjI GdCShGb GdeGdjI ef GdJdGYH aj CSYGQ GdChQGb GdeGdjI, hLGA aj aUdjf; GdChd(B: (3GdehGLgI GdJTQjYjI aj ecGaMI GdJdGYH aj CSYGQ GdChQGb GdeGdjI, hGdKGfj(B: (3OhQ GdbhGfjf aj JYRjR GdQbGHI GdEOGQjI Ydi GdCShGb GdeGdjI(B. (3hGdgOa ef cd eG Sda gh Gdhbha Ydi eUOQ GdJaGhJ Hjf KhQI GdfUhU GdbGfhfjI hGdMUjdI GdYedjI GdeJOfjI decGaMI GdJdGYH aj CSYGQ GdChQGb GdeGdjI, HGdJQcjR Ydi GdbOQ GdPj jecf Cf jQJHg GdbGfhf ef aGYdjI hEfbGP(B.s
(3CWQhMI (B((3OcJhGQg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj (B2022.s
(3HHdjhLQGajG(B: (3UaMGJ (B314-294.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdChQGb GdeGdjIs; (3GdTaGajI(B.s; (3GdJdGYH aj CSYGQ GdChQGb GdeGdjIs; (3GdbGfhf GdchjJjs; (3GdbGfhf GdEfLdjRjs; (3ecGaMI GdJdGYH ai CSYGQ GdChQGb GdeGdjIs; (3LQjeI GdJdGYH ai GSYGQ GdGhQGb GdeGdjIs; (3GdQbGHI Ydi GdCShGb GdeGdjIs; (3eHOC GdEaUGMs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs